“We Are in the Darkness”: The Impact of Fair Trade from the Perspective of Coffee Growers in the Kilimanjaro Region - Babo, Alfred (Afrika Tanulmányok / Hungarian Journal of African Studies, 2022)
Studying the impacts of Fairtrade on rural communities requires examining how Western ethical businesses and eco-friendly social movements affect farmers’ livelihoods. This research took place in coffee-growing communities in Tanzania and aimed to understand local farmers’ prospects for their collaboration with Fairtrade. Although the Fairtrade initiative aims to strengthen cultivation skills to increase the quality and price of coffee production, farmers and leaders of the rural cooperatives critically assessed the mitigated impacts of the ethical trade on the development of their lives and communities. The article, based on ethnographic research in the Moshi District, argues that beyond changes induced by the ethical business organization, farmers are trapped in “darkness” due to having insufficient information on their trading partner and limited ability to empower and transform their cooperatives.